2010
DOI: 10.1089/jop.2009.0100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated Administrations of Tafluprost, Latanoprost, and Travoprost on Optic Nerve Head Blood Flow in Conscious Normal Rabbits

Abstract: Repeated topical administration of any of the three prostaglandin F(2alpha) analogs increased ONH blood flow in rabbits, without changing heart rate. The increase in ONH blood flow induced by tafluprost was greater than that induced by latanoprost (P = 0.086) or travoprost (P = 0.037) at 60 min on day 28.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
2
26
0
3
Order By: Relevance
“…who found that ONH blood flow increased in rabbit eyes after 28 days of treatment with any of the three F 2α prostaglandin analogs (tafluprost, latanoprost, or travoprost). 24 Using laser speckle flowgraphy, the effect of tafluprost (+11.9%) on blood flow was significantly greater than that seen with travoprost (+6.7%, P=0.037) and tended to be greater than that seen with latanoprost (+7.2%, P=0.086) at 60 min on day 28 post treatment. 24 Dong et al found that tafluprost induced concentration-dependent relaxation of precontracted isolated rabbit ciliary arteries, but by a mechanism that was independent of endothelial-derived factor.…”
Section: Tafluprost Efficacy and Safety -Preclinical And Animal Studiesmentioning
confidence: 86%
See 1 more Smart Citation
“…who found that ONH blood flow increased in rabbit eyes after 28 days of treatment with any of the three F 2α prostaglandin analogs (tafluprost, latanoprost, or travoprost). 24 Using laser speckle flowgraphy, the effect of tafluprost (+11.9%) on blood flow was significantly greater than that seen with travoprost (+6.7%, P=0.037) and tended to be greater than that seen with latanoprost (+7.2%, P=0.086) at 60 min on day 28 post treatment. 24 Dong et al found that tafluprost induced concentration-dependent relaxation of precontracted isolated rabbit ciliary arteries, but by a mechanism that was independent of endothelial-derived factor.…”
Section: Tafluprost Efficacy and Safety -Preclinical And Animal Studiesmentioning
confidence: 86%
“…24 Using laser speckle flowgraphy, the effect of tafluprost (+11.9%) on blood flow was significantly greater than that seen with travoprost (+6.7%, P=0.037) and tended to be greater than that seen with latanoprost (+7.2%, P=0.086) at 60 min on day 28 post treatment. 24 Dong et al found that tafluprost induced concentration-dependent relaxation of precontracted isolated rabbit ciliary arteries, but by a mechanism that was independent of endothelial-derived factor. 25 28 In a more recent study, commercially available preservative-free tafluprost was applied directly onto the surface of a rat retinal explant culture.…”
Section: Tafluprost Efficacy and Safety -Preclinical And Animal Studiesmentioning
confidence: 86%
“…87 Prostaglandin analogues have been found to increase ONH and retinal blood flow in humans as well as in experimental animals. [88][89][90][91] In a study in healthy volunteers, 2-week administration of topical latanoprost also improved choroidal blood flow regulation during both, an experimental increase and decrease in OPP compared with placebo, but this effect is most likely related to the ocular hypotensive effect of the drug. 92 Until recently, no clinical outcome data were available for any of the prostaglandin analogues, because most of the large-scale clinical outcome trials were started before this class of antiglaucoma drugs became commercially available.…”
Section: Topical Therapiesmentioning
confidence: 99%
“…Depending on the drug or formulation used, PGAs have been reported to increase, decrease, or not affect ocular blood flow. However, the reports are conflicting, with opposing results in some cases (19,20) . In the work presented here, both tafluprost BAK-free and travoprost BAK significantly reduced the RI of the OA in rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…No effects on CDI parameters were found for topical bimatoprost BAK, travoprost POLYQUAD, or latanoprost BAK. Some research has also revealed no changes in the blood flow in the OA in humans and rabbits in response to PGAs, although some PGAs show good results in other vascular beds, such as on the optic nerve head and in the central retinal artery (20,(22)(23)(24) . Nevertheless, our research showed that the results with travoprost are controversial.…”
mentioning
confidence: 99%